STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PRODUK PENJUALAN PRODUK PADA HOME INDUSTRI KERUPUK BAWANG CAP NGEBONG SEMANDING-TUBAN - Aslam, Much Nuruddin; Unwanullah, Arif (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Marketing strategy is a very important thing in the business world. Simply put, marketing strategies are designed to increase sales by promoting goods or services with the aim of making a profit. Companies must have knowledge about marketing because it is important when faced with several problems, such as faced with declining consumer purchasing power because there are factors that influence it, such as the number of competitors and resulting in a slowdown in company growth. This research was conducted to describe the marketing strategy and sales results of the ngebong stamp garlic crackers product. And how to plan a marketing strategy to increase product sales in the Home Industry of Garlic Cap Ngebong Crackers. The approach of this study uses research methods by making direct observations to find information and evidence to clarify problems that occur in marketing strategy planning in increasing sales results. The data collection techniques used are through interviews, observation and documentation. The data analysis technique used is descriptive analysis, namely to analyze data by describing or describing the data that has been collected. The results of this study prove that implementing a marketing strategy consisting of: market segmentation, market targeting, brand strategy, pricing program, & sales program has a positive impact on the cap ngebong onion cracker home industry.